Reexamining the Schmalensee effect - Jeong-Yoo Kim; Nathan Berg (Economics: The Open-Access, Open-Assessment E-Journal, 2017)
The authors reexamine the Schmalensee effect from a dynamic perspective. Schmalsensee's argument suggesting that high quality can be signaled by high prices is based on the assumption that higher quality necessarily incurs higher production cost. In this paper, the authors argue that firms producing high-quality products have a stronger incentive to lower the marginal cost of production cost because they can then sell larger quantities than low-quality firms can. If this dynamic effect is large enough, then the Schmalensee effect degenerates and, thus, low prices signal high quality. This result is different from the Nelson effect relying on the assumption that only the high-quality product can generate repeat purchase, because the result is valid even if low-quality products can also be purchased repeatedly. The authors characterize a separating equilibrium in which a high-quality monopolist invests more to reduce cost and, as a result, charges a lower price. Separation is possible due to a difference in quantities sold in the second period across qualities.
Keywords: D82; L15; 330; experience good; quality; signal; Schmalensee effect